Pengaruh Citra Merek, Karakteristik Produk, dan Presepsi Nilai Terhadap Keputusan Toko Deliwafa Malang (Studi Kasus Mahasiswa Universitas Islam Malang) - Mumtaz, Muhammad Abdillah Hifny; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This study aims to analyze the effect of Brand Image, Product Characteristics, and Perceived Value on Purchasing Decisions at Deliwafa Stores among students of the Islamic University of Malang. The research method used is quantitative based on the philosophy of positivism. The research sample was selected using purposive sampling technique, with a total of 120 student respondents. Primary data was collected through a questionnaire that had been tested for validity and reliability. The results showed that Brand Image and Product Characteristics have a positive influence but do not have a significant influence on product purchasing decisions at Toko Deliwafa. on the other hand, perceived value has a dominant effect and has a significant positive effect, where if the higher the perceived value, the purchasing decision will increase. Overall, the combination of brand image, product characteristics, and perceived value contributed 88.7% to purchasing decisions, while the remaining 11.3% was influenced by other factors not examined in this study..Â Keywords: Brand Image, Product Characteristics, Perceived Value, Purchase Decision, Deliwafa Store, Students of Islamic University of Malang